1999
DOI: 10.1149/1.1392690
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of Thermal Runaway in Microwave Heating of Ceramics

Abstract: The steady-state behavior of a ceramic slab under microwave heating by transverse magnetic illumination is analyzed. Local bifurcation techniques are applied to a one-dimensional model to classify the region of parametric sensitivity (or thermal runaway). It is observed that for a certain set of parameters, there are periodically recurring ranges of slab thickness for which thermal runaway may be avoided. The runaway dependence on other parameters critical to the operation of the process is also studied. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[14,27,18], as shown in Figure 1. The ceramic slab with length l and relative dielectric constant ε r is assumed to be exposed to the free space.…”
Section: Microwave Heating Model On Ceramicsmentioning
confidence: 92%
See 2 more Smart Citations
“…[14,27,18], as shown in Figure 1. The ceramic slab with length l and relative dielectric constant ε r is assumed to be exposed to the free space.…”
Section: Microwave Heating Model On Ceramicsmentioning
confidence: 92%
“…The conductivity increases with the rise of temperature, which can be described by an exponential or Arrhenius model [14,18] :…”
Section: Microwave Heating Model On Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of problem statement is capable of tracing resonant effects in microwave absorption and their influence on the stability of heating. In particular, it has been shown that for a certain set of parameters, there can be periodically recurring ranges of slab thickness for which thermal runaway may be avoided …”
Section: Heat Transfer Aspects and Sintering Simulationsmentioning
confidence: 99%
“…Chatterjee, et al, [40] analyzed the microwave heating of ceramic materials by solving the equations for grain growth and porosity [54] during the late stages of sintering, coupled with the heat conduction equation and electric field equations for 1-D slabs. Gupta, et al, [41] analyzed the steady-state behavior of a ceramic slab under microwave heating by transverse magnetic illumination. They observed that for a certain set of parameters, there are periodically recurring ranges of slab thickness for which thermal runaway may be avoided.…”
Section: Application Backgroundsmentioning
confidence: 99%